Evaluation of anti-acne gel of Piper crocatum leaves ethanolic extract against Propionibacterium acnes - Mendra, Ni Nyoman Yudianti; Givanda, Jesi Dyah Ayu; Putra, Made Agus Sunadi (JURNAL ILMU KEFARMASIAN INDONESIA, 2024)
The red betel leaf (Piper crocatum) exhibited antibacterial properties by inhibiting Propionibacterium acnes, known for causing acne. The study aimed to develop an anti-acne gel formulation using Piper crocatum leaves ethanolic extract and to evaluate its antibacterial efficacy against Propionibacterium acnes. The extract was formulated into three gel formulas, with concentrations of 15%, 20%, and 25%, respectively. Antibacterial activity was evaluated using the agar well diffusion method, with Clindamycin gel as the positive control. The inhibition diameter were analyzed statistically using One Way ANOVA and Post Hoc LSD tests at a 95% confidence level. The result showed that the gel met the physical test requirements. The inhibition zone of the samples was observed with an inhibition diameter of 7.98 mm, 8.06 mm, and 8.16 mm for 15%, 20%, and 30% extract of gel, respectively, compared to the positive control 27.60 mm (p < 0,05). The research findings indicate that anti-acne gel of Piper crocatum leaves ethanolic extract exhibit moderate antibacterial activity in an in vitro setting. Statistically significant differences in inhibition diameters were observed between each gel sample and positive control.